1986
DOI: 10.1002/elps.1150070602
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of convex Ferguson plots in agarose gel electrophoresis by empirical computer modeling

Abstract: Agarose gel electrophoresis has been shown to give rise to non‐linear plots of log (mobility) vs. gel concentration of spherical viruses (Serwer,[1]) and cellular vesicles (Gottlieb et al.[2]). This finding also applies to proteins as shown in this study. Considering that in the non‐linear plot, the slope becomes a function of gel concentration, it is possible to determine particle properties and gel parameters by a modification of the conventional method derived from the Ogston theory for long‐fiber gels. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…(iii) Consistent with the widening of a stack in proportion to load of constituents [11][12][13], the fluorescently detected band increases in area with increasing load of proteins A, B and C (Fig. 3) and with increased SDS-load from 1 to 5% in the sample, the latter resulting in a 2.4-fold increase in band area.…”
Section: The Sds-protein Band Detected Fluorimetrically In the Absencsupporting
confidence: 51%
See 1 more Smart Citation
“…(iii) Consistent with the widening of a stack in proportion to load of constituents [11][12][13], the fluorescently detected band increases in area with increasing load of proteins A, B and C (Fig. 3) and with increased SDS-load from 1 to 5% in the sample, the latter resulting in a 2.4-fold increase in band area.…”
Section: The Sds-protein Band Detected Fluorimetrically In the Absencsupporting
confidence: 51%
“…(iv) Consistently with the unstacking of constituents when their net mobility is lowered below that of the trailing constituent, either by raising the gel concentration or by increasing the size of the constituent, it was found that SDS-proteins A, C and E comigrate at agarose concentrations below 4%, A and C comigrate (at reduced mobi- The initial and final slopes of the convex Ferguson plots [12] are designated KR-I and KR-II, respectively. Hypothetically, proteins A and C are stacked at all gel concentrations, while protein E is unstacked above 4% agarose concentration.…”
Section: The Sds-protein Band Detected Fluorimetrically In the Absencmentioning
confidence: 75%
“…The program SigmaPlot (Jandel Scientific) was used for curve fitting on the Macintosh computer. Figure 1 shows a representative example (phycoerythrin, R ) 4.0 nm) for the relation between the local retardation coefficient [K R ′ ) log(µ/µ 0 )/c] 18 and PEG molecular weight at a PEG concentration of 0.75%. The transition between the dilute and semidilute regimes at 0.75% PEG is shown by the arrow.…”
Section: Capillary Zone Electrophoresis (Cze)mentioning
confidence: 99%
“…Clearly, these provisos do not apply to DNA fragments, which are flexible, and do depend in their structures on field strength and gel concentration [ 11 and therefore require a future determination as to the confidence limits of their electrophoretic mobilities. Similarly, the degree of reproducibility of mobilities remains unknown for agarose gel electrophoresis at low concentrations, at which the transition from double-helical to supercoiled gel structure takes place [19].…”
Section: Inter-experimental Reproducibility Of Mobilities In Agarose mentioning
confidence: 99%